Factors which interfere in breastfeeding - Mirna Albuquerque Frota; Fabianne Lopes da Costa; Simone Dantas Soares; Osvaldo Albuquerque Sousa Filho; Conceição de Maria de Albuquerque; Cíntia Freitas Casimiro (Rev Rene)
This is a qualitative study that aimed to identify the factors related to early weaning among babies less than six months of age. The data were collected through semi-structured interviews with 20 mothers of children under six months in early weaning, in the period of August to November 2007. The results suggest some factors that interfere in the exclusive breastfeeding: misinterpretation of baby’s cry linking it to hunger; inadequacy of milk, the need for such mothers to work to help with home expenses; difficulties related to the breast; refusal to the breast from the child. It was concluded that despite the knowledge about the benefits of breast milk and the breastfeeding importance during the first six months of life, they experience some difficulties, in which it is perceived contradictions between favorable and unfavorable positions, doubts and difficulties during breastfeeding.